Environmental Regulations, Staff Quality, Green Technology, R&D Efficiency, and Profit in Manufacturing (International Journal of Innovative Research in Engineering & Management, 2021)
This research looks at environmental  regulations (ER), staff quality (SQ), R&D efficiency  (RDE), green technology (GT), and profit. In China, 1197  enterprises in 16 manufacturing sectors were investigated  between 2008 and 2015. In 2006, China surpassed the  American America as it world's largest emitters of carbon,  SO2, and ox nitride. Garbage emissions are especially bad  in cities featuring industrialized production lines. Although  China's Climate And Energy Regulation sought to lower  the percentage of GDP to greenhouse gases from 45  percent in 1996 to 40 percent from 2010 by implementing  pollution control regulations, it failed to achieve this goal  Firm RDEs are investigated using Department of  transportation benchmarks, and indeed the results show  that SQ is considered necessary for large RDE and GT (as  expected), but its primary effects are mixed. ER also has  an effect on the SQ-GT, Total area, and Total area  linkages, according to the author. If ERs are reduced, SQ,  in especially, will be of no use to GT or profit. If a firm's  SQ is at or over the ER cut-off frequency, it may increase  SQ for greater gains in GT and profits. Our results'  ramifications for theory and practice are also addressed.
Keywords: ER; Environment; Green Technology; Pollution